The Effect of Economic Growth, Inflation and Decent Living Needs on Provincial Minimum Wages in Kalimantan Island - Resti Amelia (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
This study aims to analyze the effect of the variables of economic growth, inflation, decent living needs partially and simultaneously on the Provincial Minimum Wage in Kalimantan Island in 2010-2019. The data in this study uses secondary data sourced from the Indonesian Central Statistics Agency (BPS). The analysis used in this study is multiple linear regression analysis of panel data with the Eviews program. The results of this study indicate that economic growth has a negative and insignificant effect on the Provincial Minimum Wage in Kalimantan Island, inflation has a negative and significant effect on the Provincial Minimum Wage on Kalimantan Island, the need for decent living has a positive and significant effect on the Provincial Minimum Wage on Kalimantan Island and the need for decent living is the most dominant factor influencing the provincialminimum wage on the island of Kalimantan and the results of the study This shows that economic growth, inflation and the need for decent living simultaneously or jointly affect the Provincial Minimum Wage on the island of Kalimantan.